Social Integration of the Polish National Minority in Lithuania - S. S. Starovoitova; L. A. Lebedintseva (Дискурс)
Introduction. This article aims to examine social integration of national minorities in Lithuania. The scientific novelty of this study represents identification of the main social mechanisms that influence the integration of national minorities. The author focuses on the integration of Polish minority due to their large number and active political position.Methodology and sources. Throughout the study, big attention was paid to the scientific articles and monographs of Lithuanian sociologists, thanks to which the term “social integration” in relation to the Lithuanian case, the identity of the Poles living in Lithuania, as well as the integration of national minorities into Lithuanian society through the education system were studied. Moreover, expert and narrative interviews with representatives of the Polish minority were conducted in order to better understand the situation.Results and discussion. Based on the data, the authors came to the conclusion that current legislation creates favorable conditions for the protection of the rights of national minorities, contributes to the preservation of their identity and development of culture. However, representatives of national minorities express the desire to have a separate law on national minorities that would clearly define and regulate their rights. Lithuanian language skills are seen as an important indicator evaluating integration of national minorities.Conclusion. The education system creates opportunities for national minorities to acquire necessary competencies and learn Lithuanian language. Communication contributes to the improvement of language skills. Good knowledge of Lithuanian language contributes to the expansion of the circle of contacts and integration into the Lithuanian social system.